Land Occupations Are Back in Chile. Reflections on Urban Informality; [Le Occupazioni Di Terreno Sono Tornate in Cile. Riflessioni Sull’Informalità Urbana] - Braithwaite-Castillo, S (FrancoAngeli, 2022)
Informal settlements in Chile have begun to grow again, especially in the last three years, after decades in which they had steadily declined. What is the reason for this sudden increase? Many have pointed to structural causes, such as migration or rising rental and housing prices. In line with a recent literature on urban informality, in this article we offer an alternative reading, attentive to relations with institutions and the political system. Through interviews, document and press reviews, we support the thesis that the explosive increase that has occurred in recent years is closely linked to the social and political crisis caused by the protests that erupted in October 2019. © FrancoAngeli. This work is released under Creative Commons Attribution - Non-Commercial – No Derivatives License.